Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

 Shauna solve the polynomial equations given in the table determine whether each polynomial is correct select correct or incorrect for each equation

Shauna Solve The Polynomial Equations Given In The Table Determine Whether Each Polynomial Is Correct Select Correct Or Incorrect For Each Equation class=

Sagot :

Answer:

correct / incorrect / incorrect

Step-by-step explanation:

5a - 8 + 2a² + 2a - 1 ← collect like terms

= 2a² + 7a - 9 ← correct

-------------------------------------

b² + 6b - 4 - (3b + b²) ← distribute parenthesis by - 1

= b² + 6b - 4 - 3b - b² ← collect like terms

= 3b - 4 ≠ 2b² + 3b - 4

---------------------------------------

9c - 4c² - (2c² + c) ← distribute parenthesis by - 1

= 9c - 4c² - 2c² - c ← collect like terms

= - 6c² + 8c ≠ - 6c² + 10c

Answer:

correct

incorrect

incorrect

Step-by-step explanation:

[tex]\begin{aligned}(5a-8)+(2a^2+2a-1)&=5a-8+2a^2+2a-1\\& = 2a^2+5a+2a-8-1\\ & = 2a^2+7a-9\end{aligned}[/tex]

[tex]\implies (5a-8)+(2a^2+2a-1)=2a^2+7a-9\quad\textsf{is correct}[/tex]

---------------------------------------------------------------------------------------

[tex]\begin{aligned}(b^2+6b-4)-(3b+b^2) &=b^2+6b-4-3b-b^2\\ & = b^2-b^2+6b-3b-4\\& = 3b-4\end{aligned}[/tex]

[tex]\implies (b^2+6b-4)-(3b+b^2)=2b^2+3b-4\quad\textsf{is incorrect}[/tex]

---------------------------------------------------------------------------------------

[tex]\begin{aligned}(9c-4c^2)-(2c^2+c) &=9c-4c^2-2c^2-c\\ & = -4c^2-2c^2+9c-c\\& = -6c^2+8c\end{aligned}[/tex]

[tex]\implies (9c-4c^2)-(2c^2+c)=-6c^2+10c\quad\textsf{is incorrect}[/tex]